2016
DOI: 10.1021/acs.jmedchem.6b00639
|View full text |Cite
|
Sign up to set email alerts
|

Probing Lipophilic Adamantyl Group as the P1-Ligand for HIV-1 Protease Inhibitors: Design, Synthesis, Protein X-ray Structural Studies, and Biological Evaluation

Abstract: A series of potent HIV-1 protease inhibitors with a lipophilic adamantyl P1 ligand have been designed, synthesized and evaluated. We have developed an enantioselective synthesis of adamantane-derived hydroxyethylamine isostere utilizing Sharpless asymmetric epoxidation as the key step. Various inhibitors incorporating P1-adamanylmethyl in combination with P2-ligands such as 3-(R)-THF, 3-(S)-THF, bis-THF and THF-THP were examined. The S1′ pocket was also probed with phenyl and phenylmethyl ligands. Inhibitor 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Experimental details, spectral data, and 1 H and 13 C NMR spectra of all new compounds (PDF) FAIR data, including the primary NMR FID files, for compounds [3][4][5][6][7][8][9][11][12][13][14][15][16][18][19][20][21][22][23]…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental details, spectral data, and 1 H and 13 C NMR spectra of all new compounds (PDF) FAIR data, including the primary NMR FID files, for compounds [3][4][5][6][7][8][9][11][12][13][14][15][16][18][19][20][21][22][23]…”
Section: * Sı Supporting Informationmentioning
confidence: 99%
“…A number of multidrug-resistant PIs, such as Darunavir, a new front-line therapy for HIV/AIDS, possess a unique (3 R ,3a S ,6a R )-hexahydro-furo-[2,3- b ]­furan-3-ol ( bis -THF) fragment (structure A, Figure ). SAR (Structure–activity relationship) studies revealed that synthetic analogs possessing THF-THP (structure B, Figure ) or a THP-THF bicyclic ring (structure C, Figure ) also exhibited interesting inhibitory effects …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to PR inhibitors mainly results from residue substitutions. Among these mutated residues, single mutations of certain conserved residues can reduce the binding of inhibitors to PR, while most double-mutant and multiple-mutant PRs bring about strong resistance toward inhibitors. , Therefore, there is an increasing need to develop new anti-AIDS inhibitors that can effectively reduce the resistance of mutants. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus far, HIV-1 protease inhibitors (PIs) approved by the FDA have increased the life expectancy significantly and reduced the mortality dramatically. However, the emergence of drug-resistant HIV-1 variants posed a threat to further treatment. And what’s worse, Darunavir (DRV, 1 , Figure ), with a high genetic barrier to many multidrug-resistant (MDR) protease variants, has emerged highly DRV-resistant HIV-1 variants in treatment-experienced patients. , Notably, DRV was incapable of combating the identified mutations. , Although great effort has been made to explore potent PIs, none of them were found to inhibit DRV-resistant HIV-1 variants effectively. Hence, the discovery of novel PIs with high genetic barrier against DRV-resistant HIV-1 variants is highly urgent.…”
mentioning
confidence: 99%